Validation of multiple myeloma risk stratification indices in routine clinical practice: Analysis of data from the Czech Myeloma Group Registry of Monoclonal Gammopathies - Radocha, Jakub; Maisnar, Vladimír; Pour, Luděk; Špička, Ivan; Minařík, Jiři; Szeligová, Lenka; Pavlíček, Petr; Jungová, Alexandra; Krejčí, Marta; Pika, Tomáš; Straub, Jan; Brožová, Lucie; et al. (Cancer medicine, 2018)
This study used data from the Czech Myeloma Group Registry of Monoclonal Gammopathies to validate the International Myeloma Working Group (IMWG) and revised International Staging System (R-ISS) indices for risk stratification in patients with multiple myeloma (MM) in clinical practice. Patients were included if they had symptomatic MM, complete data allowing R-ISS and IMWG staging (including cytogenetic information regarding t(4;14), t(14;16), and del(17p)), and key parameters for treatment evaluation. Median overall survival (OS) in included patients (n = 550) was 47.7 (95% CI: 39.5-55.9) and 46.2 (95% CI: 38.9-53.5) months from diagnosis and initiation of first-line therapy, respectively. Patients categorized as higher vs lower risk had reduced survival; median OS from diagnosis was 35.4 (95% CI: 30.5-40.3) vs 58.3 (95% CI: 53.8-62.9) months in high-risk vs other patients (IMWG; P = .001) and 34.1 (95% CI: 30.2-38.0) vs 47.2 (95% CI: 43.4-51.0) months in Stage III vs Stage II patients (R-ISS; P < .001). In conclusion, IMWG and R-ISS risk stratification indices are applicable to patients with MM in a real-world setting.
Keywords: senioři; Paraproteinemias; analýza přežití; real-world; senioři nad 80 let; Multiple Myeloma; Retrospective Studies; Survival Analysis; Česká republika; Risk Assessment; Middle Aged; registrace; mužské pohlaví; Adult; Czech Republic; Registries; paraproteinemie; Czech Myeloma Group Registry; Aged, 80 and over; Neoplasm Staging; mnohočetný myelom; ženské pohlaví; monoclonal gammopathies; hodnocení rizik; retrospektivní studie; Humans; Practice Patterns, Physicians'; lidé středního věku; rizikové faktory; multiple myeloma; staging nádorů; dospělí; Female; Aged; Risk Factors; risk stratification; overall survival; lékařská praxe - způsoby provádění; lidé; Male